CHARACTERIZATION OF SECONDARY METABOLITES IN THE DICHLOROMETHANE FRACTION OF BLACK SEA CUCUMBER (Holothuria atra) FROM THE WATERS OF LEMUKUTAN ISLAND, WEST KALIMANTAN - Ananda Rahmadanti; Afghani Jayuska; Ajuk Sapar; Endah Sayekti (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2026)
The black sea cucumber (Holothuria atra) is a marine organism from the family Holothuridae that serves as a source of raw material for medicinal development and is abundant in the waters around Lemukutan Island, West Kalimantan. This study aims to isolate and identify secondary metabolites from the dichloromethane fraction of black sea cucumber from Lemukutan Island using FTIR and 1H-NMR. The steps involved in this study include extraction (maceration and partitioning), phytochemical testing, fractionation (column chromatography), and the isolation and identification of molecular structures. Phytochemical testing of the dichloromethane fraction of H. atra revealed the presence of secondary metabolite compounds belonging to the saponin, phenolic, and alkaloid groups. Characterization of the compounds in the dichloromethane fraction using FTIR revealed peaks at wavenumbers 3376.54 cm⁻¹  (-OH stretch), 2855.38–2955.44 cm⁻¹  (-CH aliphatic), 1730.81 cm⁻¹  (C=O), 1635.43 cm⁻¹(C=C), 1463.99 cm⁻¹(C-H methylene), 1126.14 cm⁻¹(C-O), and 1053.64 cm⁻¹(C-C). The results of the isolate identification using 1 H-NMR (500 MHz, CDCl3 ) shows the presence of peaks at chemical shifts (δ) 0.68 ppm (1H, t), 0.84 ppm (9H, m), 1.19–1.24 ppm (22H, m), 1.44 ppm (1H, m), 1.55 ppm (3H, m), 1.95 (1H, s), 4.09 ppm (41H, s), 7.07 ppm (1H, d, J=8.15 Hz), and 7.68 ppm (1H, d, J=6.9 Hz), which are characteristic of bis(2-ethylhexyl) 3-hydroxy-6-methyl phthalate compounds.